2004
DOI: 10.3928/1081-597x-20040501-03
|View full text |Cite
|
Sign up to set email alerts
|

Total and Corneal Optical Aberrations Induced by Laser in situ Keratomileusis for Hyperopia

Abstract: PURPOSE: To evaluate changes induced by standard laser in situ keratomileusis (LASIK) for hyperopia on total and corneal optical quality. METHODS: Total and corneal aberrations were measured before and after standard hyperopic LASIK in 13 eyes (preoperative spherical equivalent refractive error +3.17 ± 1.10 D). The Chiron Technolas 217C laser with PlanoScan was used. Total aberrations (measured using laser ray tracing) and corneal aberrations (estimated from a videokeratoscope) were described using Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 35 publications
4
45
0
3
Order By: Relevance
“…Bueeler et al 8 reported that it was unlikely that optical quality would deteriorate if the lateral alignment error was within 0.45 mm. Llorente et al 9 reported that, in 90% of eyes, even an accuracy of 0.80 mm or better would be sufficient. However, many patients who complain of visual disturbances after refractive surgeries have visual acuities of 1.0 or better and refractions close to plano.…”
Section: Discussionmentioning
confidence: 98%
“…Bueeler et al 8 reported that it was unlikely that optical quality would deteriorate if the lateral alignment error was within 0.45 mm. Llorente et al 9 reported that, in 90% of eyes, even an accuracy of 0.80 mm or better would be sufficient. However, many patients who complain of visual disturbances after refractive surgeries have visual acuities of 1.0 or better and refractions close to plano.…”
Section: Discussionmentioning
confidence: 98%
“…Aberrations increase following hypermetropic corneal refractive surgery 173,174 (Figure 9a). Anterior corneal spherical aberration is positive before surgery and becomes negative after surgery ( Figure 9b), with the change increasing with the magnitude of correction.…”
Section: Corneal Refractive Surgerymentioning
confidence: 99%
“…This is because anterior corneas become more prolate following treatment. 173,[175][176][177] As an example of the magnitude of the changes, Llorente and colleagues 173 found that mean anterior corneal and total RMS higher-order aberrations increased following LASIK by 1.8 and 2.2 times, respectively and the mean spherical aberration co-efficient c 4 0 decreased by 0.70 ± 0.30 µm (pre-surgical mean spherical equivalent +3.2 ± 1.1 D, 6.5 mm pupil).…”
Section: Corneal Refractive Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…7 Most problems, especially under mesopic or scotopic conditions 8 are related to a decrease in optical quality due to a significant increment of ocular aberrations after surgery. [9][10][11][12] The increase of spherical-like aberrations after LASIK is due to the ablation profile and corneal reflection losses of the laser beam, [13][14][15] while the increase of coma-like aberrations seem to be mainly related to ablation decentrations. 16 An increase of ocular aberrations may not be always related to an increase of corneal aberrations, but to a disruption of the fine balance of the aberrations of the corneal and the lens.…”
Section: Introductionmentioning
confidence: 99%